A novel null HLA allele, HLA‐DRB1*15:115N, identified in a Chinese family. Issue 1 (30th April 2015) - Li, X.; Zou, H.; Li, M.; Chen, Q.
<x xml:space="preserve">Abstract</x> The novel allele HLA‐DRB1*15:115N differs from HLA‐B*15:80N by a nucleotide substitution at position 227 T > A.